2013
DOI: 10.1186/1756-0500-6-72
|View full text |Cite
|
Sign up to set email alerts
|

The illusion of specific capture: surface and solution studies of suboptimal oligonucleotide hybridization

Abstract: BackgroundHybridization based assays and capture systems depend on the specificity of hybridization between a probe and its intended target. A common guideline in the construction of DNA microarrays, for instance, is that avoiding complementary stretches of more than 15 nucleic acids in a 50 or 60-mer probe will eliminate sequence specific cross-hybridization reactions. Here we present a study of the behavior of partially matched oligonucleotide pairs with complementary stretches starting well below this thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Our overall aim was to capture distantly related exogenous retroviral sequences in complex samples from humans. Even short complementary regions may mediate hybridization between capture probes and targets 18 19 within the host genome e.g. orthologous genes and human endogenous retrovirus (HERV) sequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our overall aim was to capture distantly related exogenous retroviral sequences in complex samples from humans. Even short complementary regions may mediate hybridization between capture probes and targets 18 19 within the host genome e.g. orthologous genes and human endogenous retrovirus (HERV) sequences.…”
Section: Resultsmentioning
confidence: 99%
“…Most methods are dependent on stringent reaction conditions for discrimination between correct target and competing irrelevant sequences with varying similarity. Kane et al established that cross hybridization may happen if nucleotide sequence similarity exceeds around 75% 18 , unless carefully controlled 19 . Matching stretches of as little as 12–15 complementary nucleotides are sufficient to mediate unspecific cross-hybridization of 50-bp oligonucleotides 18 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such duplexes formed when only 12 bp of complementary sequence were present. Surface hybridization experiments have confirmed that a signal indistinguishable from a full-strength signal arising from a low copy number PM can be obtained from sequences that form only a partial duplex (63). …”
Section: Optimizing Suboptimal Probesmentioning
confidence: 88%
“…A number of studies have analyzed factors that influence genome-wide cross-hybridization levels of microarray probes. Duplexes of 10–16 nucleotides that are complementary to targets may be sufficient to generate a cross-hybridization signal [ 27 28 ]. For 50-nt probes in particular, it was noted that “a complementary stretch of nucleotides as short as 12 nucleotides may result in the appearance of significant signal from an unintended binding partner” [ 28 ].…”
Section: Introductionmentioning
confidence: 99%